Neuroinflammation in glaucoma: a myriad of cellular pathways and players - Michael MacLean; Sean D. Lydon; Cátia Gomes; Elizabeth M. Pizzi; Cory A. Diemler; Sarah E. R. Yablonski; Gareth R. Howell; Jason S. Meyer; Richard T. Libby (Mammalian Genome, 2026)
Glaucoma is a complex neurodegenerative disease with multiple subtypes, yet all are characterized by the progressive dysfunction and loss of retinal ganglion cells (RGCs), which ultimately results in vision impairment and blindness. Elevated intraocular pressure (IOP) is a major risk factor for glaucoma; however, it is neither necessary nor sufficient for glaucomatous neurodegeneration, as patients can exhibit high IOP without developing glaucoma and patients can develop glaucoma with normal IOP. Yet FDA-approved treatment options are largely limited to approaches to minimize risk and reduce IOP. Thus, there is a critical need to target other aspects of glaucoma pathophysiology. Neuroinflammation is broadly defined here as immune-relevant responses, often involving microglia and astrocytes, within the central nervous system which may include peripheral immune cell infiltration. Burgeoning evidence has implicated glia in the development and progression of glaucoma in human tissues and mouse models. Most mouse models of glaucoma to date have shown that microglia and astrocytes are reactive in early stages of glaucomatous neurodegeneration prior to overt RGC loss. However, there is growing evidence that human and mouse glia adopt distinct phenotypes in response to neurodegeneration. Thus, there is critical need to expand our studies to include the new generations of human cell culture models. In this review, we discuss: 1) the evidence of neuroinflammatory processes in human glaucoma; 2) models of glaucoma relevant neuroinflammation; and the evidence specifically for 3) innate immune cell-driven and 4) macroglia-driven processes.

Maternal care and early rearing environment influence puppy behaviour and cognition - Emily E. Bray; Laura E.L.C. Douglas; Kerinne M. Levy; Gitanjali E. Gnanadesikan; Daniel J. Horschler; Brenda S. Kennedy; Evan L. MacLean (Animal Behaviour, 2026)

Adaptive area-wide management for suppressing spruce budworm outbreaks: effectiveness of the early intervention strategy - Rob C. Johns; S. Edwards; L. Amos-Binks; J. J. Bowden; D. Carleton; C. Edge; C. Hennigar; P. James; D. MacLean; V. Martel; E. R. D. Moise; B. Morin; et al. (Journal of Pest Science, 2026)
In eastern North America, two main insecticide-based strategies are used to manage spruce budworm ( Choristoneura fumiferana ) outbreaks. The traditional ‘Foliage Protection Strategy’ (FPS) focuses on temporarily reducing defoliation and tree mortality in high-value stands, allowing outbreaks to progress naturally in surrounding areas. The ‘Early Intervention Strategy’ (EIS) is an adaptive, area-wide management approach that targets low-density “hotspots” to prevent outbreak growth and spread. We report findings from a 10-year case study (2015–2024) in Atlantic Canada assessing EIS effectiveness. EIS treatments consistently reduced population growth rates, resulting in a 12–67% reduction in hotspot areas compared to untreated areas. Crucially, this suppression curbed the rise and spread of the outbreak across northern New Brunswick, with negligible defoliation observed throughout the study period. By comparison, in a neighboring Quebec study area contemporaneously managed with FPS, the outbreak advanced normally, causing moderate to severe defoliation over ~ 1.7 million hectares by 2024. Moreover, EIS required ~ 80% less insecticide, with 66% of treated areas receiving treatment in only a single year, compared with just 15% under FPS. Our findings provide robust evidence for the effectiveness of EIS when implemented under suitable conditions, highlighting its potential as a proactive outbreak management approach.

Indiscriminate sociality: puppies do not preferentially re-engage a human partner after joint social play is interrupted - Dara S. Jonkoski; Laura E.L.C. Douglas; Daniel J. Horschler; Alyssa M. Klensin; Brenda S. Kennedy; Evan L. MacLean; Emily E. Bray (Animal Behaviour, 2026)

Functional assessments of short-term spatial memory in the Dog Aging Project identify strong associations with age that are not moderated by body mass - Stephanie H. Hargrave; Amber J. Keyser; Emma Kristal; Gene E. Alexander; Theadora A. Block; Emily E. Bray; Laura E. L. C. Douglas; Brenda S. Kennedy; Daniel E. L. Promislow; David A. Raichlen; Dog Aging Project Consortium; Evan L. MacLean (GeroScience, 2025)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

Behavioural thermoregulation compensates for changes in solar insolation in a wild insect - Alexandra S. Gardner; Ruonan Li; Jessica Jones; Rebecca Rogers; Mollie Townsend; Rolando Rodríguez-Muñoz; Paul E. Hopwood; Ilya M.D. Maclean; Tom Tregenza (Animal Behaviour, 2024)

A new Neu—a syngeneic model of spontaneously metastatic HER2-positive breast cancer - Aaron G. Baugh; Edgar Gonzalez; Valerie H. Narumi; Jesse Kreger; Yingtong Liu; Christine Rafie; Sofi Castanon; Julie Jang; Luciane T. Kagohara; Dimitra P. Anastasiadou; James Leatherman; Todd Armstrong; et al. (Clinical & Experimental Metastasis, 2024)
Metastatic disease results from the dissemination of tumor cells beyond their organ of origin to grow in distant organs and is the primary cause of death in patients with advanced breast cancer. Preclinical murine models in which primary tumors spontaneously metastasize are valuable tools for studying metastatic progression and novel cancer treatment combinations. Here, we characterize a novel syngeneic murine breast tumor cell line that provides a model of spontaneously metastatic neu-expressing breast cancer with quicker onset of widespread metastases after orthotopic mammary implantation in immune-competent NeuN mice. The NT2.5-lung metastasis (-LM) cell line was derived from serial passaging of tumor cells that were macro-dissected from spontaneous lung metastases after orthotopic mammary implantation of parental NT2.5 cells. Within one week of NT2.5-LM implantation, metastases are observed in the lungs. Within four weeks, metastases are also observed in the bones, spleen, colon, and liver. We demonstrate that NT2.5-LM metastases are positive for NeuN—the murine equivalent of human epidermal growth factor 2 (HER2). We further demonstrate altered expression of markers of epithelial-to-mesenchymal transition (EMT), suggestive of their enhanced metastatic potential. Genomic analyses support these findings and reveal enrichment in EMT-regulating pathways. In addition, the metastases are rapidly growing, proliferative, and responsive to HER2-directed therapy. The new NT2.5-LM model provides certain advantages over the parental NT2/NT2.5 model, given its more rapid and spontaneous development of metastases. Besides investigating mechanisms of metastatic progression, this new model may be used for the rationalized development of novel therapeutic interventions and assessment of therapeutic responses.

Characterizing dog cognitive aging using spontaneous problem-solving measures: development of a battery of tests from the Dog Aging Project - Stephanie H. Hargrave; Emily E. Bray; Stephanie McGrath; Gene E. Alexander; Theadora A. Block; Naomi Chao; Martin Darvas; Laura E. L. C. Douglas; Janet Galante; Brenda S. Kennedy; Breonna Kusick; Julie A. Moreno; et al. (GeroScience, 2024)

Network Analysis Reveals Changes in Dietary Intakes and DNA Methylation in Inflammatory and Obesity-related Cancer Pathways Are Associated with Improvements in Clinical Health Indicators During Behavioral Weight Loss - E. Hill; J. Siebert; I. Konigsberg; P. Jambal; M. Stanislawski; D. Ostendorf; K. Bing; L. Wayland; J. Scorsone; D. Bessesen; P. MacLean; E. Melanson; et al. (Journal of the Academy of Nutrition and Dietetics, 2023)

Associations between physical activity and cognitive dysfunction in older companion dogs: results from the Dog Aging Project - Emily E. Bray; David A. Raichlen; Kiersten K. Forsyth; Daniel E. L. Promislow; Gene E. Alexander; Evan L. MacLean; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; et al. (GeroScience, 2023)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Accounting for inter‐annual variability alters long‐term estimates of climate suitability - Alexandra S. Gardner; Kevin J. Gaston; Ilya M. D. Maclean (Journal of Biogeography, 2021)
Aim Species respond to environmental conditions and so reliable assessments of climate suitability are important for predicting how climate change could alter their distributions. Long‐term average climate data are often used to evaluate the climate suitability of an area, but in these aggregated climate datasets, inter‐annual variability is lost. Due to non‐linearity in species’ biological responses to climate, estimates of long‐term climate suitability from average climate data may be biased and so differ from estimates derived from the average annual suitability over the same period (average response). We investigate the extent to which such differences manifest in a regional assessment of climate suitability for 255 plant species across two 17‐year time periods. Location Cornwall in South‐West England provides a case study. Taxon Plantae. Methods We run a simple mechanistic climate suitability model and derive quantitative estimates of climate suitability for 1984–2000 and 2001–2017. For each period, we run the model using climate data representing average monthly values for that period. We then run the model for each year using monthly climate data for that year and average the annual suitability scores across each period (average response). We compare estimates of climate suitability from these two approaches. Results Average climate data gave higher estimates of suitability than the average response, suggesting bias against years of poor suitability in temporally aggregated climate datasets. Differences between suitability estimates were larger in areas of high climate variability and correlated with species’ environmental requirements, being larger for species with small thermal niches and narrow ranges of precipitation tolerance. Main Conclusions Incorporating inter‐annual variability into climate suitability assessments or understanding the extent to which average climate data might obscure this variance will be important to predict reliably the impacts of climate change on species distributions and should be considered when using mechanistic species distribution models.

Global variation in diurnal asymmetry in temperature, cloud cover, specific humidity and precipitation and its association with leaf area index - Daniel T. C. Cox; Ilya M. D. Maclean; Alexandra S. Gardner; Kevin J. Gaston (Global Change Biology, 2020)
The impacts of the changing climate on the biological world vary across latitudes, habitats and spatial scales. By contrast, the time of day at which these changes are occurring has received relatively little attention. As biologically significant organismal activities often occur at particular times of day, any asymmetry in the rate of change between the daytime and night‐time will skew the climatic pressures placed on them, and this could have profound impacts on the natural world. Here we determine global spatial variation in the difference in the mean annual rate at which near‐surface daytime maximum and night‐time minimum temperatures and mean daytime and mean night‐time cloud cover, specific humidity and precipitation have changed over land. For the years 1983–2017, we derived hourly climate data and assigned each hour as occurring during daylight or darkness. In regions that showed warming asymmetry of >0.5°C (equivalent to mean surface temperature warming during the 20th century) we investigated corresponding changes in cloud cover, specific humidity and precipitation. We then examined the proportional change in leaf area index (LAI) as one potential biological response to diel warming asymmetry. We demonstrate that where night‐time temperatures increased by >0.5°C more than daytime temperatures, cloud cover, specific humidity and precipitation increased. Conversely, where daytime temperatures increased by >0.5°C more than night‐time temperatures, cloud cover, specific humidity and precipitation decreased. Driven primarily by increased cloud cover resulting in a dampening of daytime temperatures, over twice the area of land has experienced night‐time warming by >0.25°C more than daytime warming, and has become wetter, with important consequences for plant phenology and species interactions. Conversely, greater daytime relative to night‐time warming is associated with hotter, drier conditions, increasing species vulnerability to heat stress and water budgets. This was demonstrated by a divergent response of LAI to warming asymmetry.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

A new system to classify global climate zones based on plant physiology and using high temporal resolution climate data - Alexandra S. Gardner; Ilya M. D. Maclean; Kevin J. Gaston (Journal of Biogeography, 2020)
Aim Climate classification systems (CCSs) can be used to predict how species’ distributions might be altered by climate change and to increase the reliability of these estimates is an important goal in biogeographical research. We produce an objective, global climate classification system (CCS) at high temporal resolution based on plant physiology as a robust way to predict how climate change may impact terrestrial biomes. Location Global Taxon Plantae Methods We construct ten climate variables that capture the physiological processes that determine plant distributions and use cluster analysis to present a new global CCS which accounts for variation in these aspects of climate. We use Kappa statistics to compare the distribution of climate zones in a five‐ and six‐cluster CCS constructed using the physiology variables to the popular Köppen‐Geiger and Köppen‐Trewartha CCSs, respectively, and find good correlation in both cases. Results Our CCS highlights ten climate zones for plants. We show that clustering of the physiologically relevant variables reproduces known, present‐day patterns of vegetation but also indicates important areas where zone assignment in our physiological CCSs is different to that of the Köppen systems. Main conclusions The existing Köppen CCSs do not entirely reflect the physiological processes that determine plant distributions. Predictions of climate‐driven changes in plant distributions may thus be unreliable in areas where zone assignment by clustering of physiologically relevant variables is different to that of the Köppen systems. Both the physiological relevance and temporal resolution of climate variables used to construct CCSs should be considered in order to predict reliably how climate change may alter plant distributions and to support an appropriate global response to conserve plant biodiversity for the future.

Going the Distance: Influence of Distance Between Boat Noise and Nest Site on the Behavior of Paternal Smallmouth Bass - K. MacLean; T. S. Prystay; M. J. Lawrence; A. J. Zolderdo; L. F. G. Gutowsky; E. Staaterman; A. J. Gallagher; S. J. Cooke (Water, Air, & Soil Pollution, 2020)

Lack of susceptibility in neonatally infected rhesus macaques to simian immunodeficiency virus-induced encephalitis - Elizabeth Delery; Diana G. Bohannon; Derek L. Irons; Carolina Allers; Chie Sugimoto; Yanhui Cai; Kristen M. Merino; Angela M. Amedee; Ronald S. Veazey; Andrew MacLean; Marcelo J. Kuroda; Woong-Ki Kim (Journal of NeuroVirology, 2019)

Correction of a Non-orthogonal, Three-Component Sonic Anemometer for Flow Distortion by Transducer Shadowing - T. W. Horst; S. R. Semmer; G. Maclean (Boundary-Layer Meteorology, 2015)
We propose that flow distortion within a non-orthogonal CSAT3 sonic anemometer is primarily due to transducer shadowing, which is caused by wakes in the lee of the acoustic transducers impinging on their measurement paths. The dependence of transducer shadowing on sonic path geometry, wind direction and atmospheric stability is investigated with simulations that use surface-layer data from the Horizontal Array Turbulence Study (HATS) field program and canopy roughness-sublayer data from the CHATS (Canopy HATS) field program. We demonstrate the efficacy of correcting the CSAT3 for transducer shadowing with measurements of its flow distortion in the NCAR wind tunnel, combined with 6 months of data collected in the atmospheric surface layer with adjacent CSAT3 and orthogonal ATI-K sonic anemometers at the NCAR Marshall field site. CSAT3 and ATI-K measurements of the variance of vertical velocity $$σ _w^2$$ σ w 2 and the vertical flux of sonic temperature agree within 1 % after correction of both sonics for transducer shadowing. Both the simulations of transducer shadowing and the comparison of CSAT3 and ATI-K field data suggest a simple, approximate correction of CSAT3 surface-layer scalar fluxes with an increase on the order of 4–5 %, independent of wind direction and atmospheric stability. We also find that $$σ _w/u_*$$ σ w / u ∗ (where $$u_*$$ u ∗ is the friction velocity) and $$r_{uw}$$ r u w (the correlation coefficient) calculated with corrected CSAT3 data are insensitive to wind direction and agree closely with known values of these dimensionless variables for neutral stratification, which is evidence for the efficacy of the correction of the horizontal wind components for transducer shadowing as well.

Storm-induced shifts in optimal nesting sites: a potential effect of climate change - David N. Bonter; Sarah A. MacLean; Shailee S. Shah; Michelle C. Moglia (Journal of Ornithology, 2014)

N-acetyl-4-aminophenol and musculoskeletal adaptations to resistance exercise training - Catherine M. Jankowski; Wendolyn S. Gozansky; Paul S. MacLean; Benjamin Shulman; Pamela Wolfe; Robert S. Schwartz; Wendy M. Kohrt (European Journal of Applied Physiology, 2013)

Requirements for labelling forest polygons in an object-based image analysis classification - Meghan Graham MacLean; Michael J. Campbell; Daniel S. Maynard; Mark J. Ducey; Russell G. Congalton (International Journal of Remote Sensing, 2013)

Ova fecundity in Scottish Atlantic salmon Salmo salar : predictions, selective forces and causal mechanisms - P. J. Bacon; J. C. MacLean; I. A. Malcolm; W. S. C. Gurney (Journal of Fish Biology, 2012)
Ova fecundities of Scottish Atlantic salmon Salmo salar , predicted from log 10 regression of ova numbers and female fork length ( L F ), differed widely between upland and lowland stocks within the same river, whereas sea‐age, river and year factors had insignificant effects on fecundity once L F was accounted for. For upland fish, the relationship between log 10 L F and log 10 ova mass ( M O ) was stable between two datasets collected 40 years apart. Although upland and lowland females both produced comparable log 10 M O (log 10 L F ) −1 , lowland females partitioned this into 45% more, but smaller ova, whereas upland females produced fewer, but larger, eggs. The possible causes and implications of this are discussed for evolutionary perspectives (lifetime production), population structure (local tributary v. large catchments; environmental effects), population dynamics and stability (density‐dependent control mechanisms) and fisheries management (stock–recruitment; short and long‐term stock sustainability).

Varying sediment sources (Hudson Strait, Cumberland Sound, Baffin Bay) to the NW Labrador Sea slope between and during Heinrich events 0 to 4 - J. T. Andrews; D. C. Barber; A. E. Jennings; D. D. Eberl; B. Maclean; M. E. Kirby; J. S. Stoner (Journal of Quaternary Science, 2012)
Core HU97048‐007PC was recovered from the continental Labrador Sea slope at a water depth of 945 m, 250 km seaward from the mouth of Cumberland Sound, and 400 km north of Hudson Strait. Cumberland Sound is a structural trough partly floored by Cretaceous mudstones and Paleozoic carbonates. The record extends from ∼10 to 58 ka. On‐board logging revealed a complex series of lithofacies, including buff‐colored detrital carbonate‐rich sediments [Heinrich (H)‐events] frequently bracketed by black facies. We investigate the provenance of these facies using quantitative X‐ray diffraction on drill‐core samples from Paleozoic and Cretaceous bedrock from the SE Baffin Island Shelf, and on the

Applying a Spruce Budworm Decision Support System to Maine: Projecting Spruce-Fir Volume Impacts under Alternative Management and Outbreak Scenarios - Chris R. Hennigar; Jeremy S. Wilson; David A. MacLean; Robert G. Wagner (Journal of Forestry, 2011)
Spruce budworm (SBW) infestations and defoliation in forests of eastern North America (e.g., 1910s, 1940s, and 1970‐1980s) have had significant negative impacts on growth and survival of spruce and fir. The Spruce Budworm Decision Support System (SBWDSS), originally developed by the Canadian Forest Service, can assist with SBW management planning by estimating the marginal timber supply (in cubic meters per hectare) benefits of protecting stands against budworm defoliation. We applied the SBWDSS to Maine and for two private forests (≈10,000-ha townships) to assess potential spruce-fir losses. Application of the approach across diverse forest types and data sets revealed dramatic differences in potential volume impacts between the two townships. The statewide analysis suggested that over 4 million ha of Maine's forest are vulnerable to the budworm. Projections of moderate and severe intensity outbreaks reduced statewide spruce-fir inventories by 20‐30% over the next 10 years.

MCP-3/CCL7 production by astrocytes: implications for SIV neuroinvasion and AIDS encephalitis - Nicole A. Renner; Nathan S. Ivey; Rachel K. Redmann; Andrew A. Lackner; Andrew G. MacLean (Journal of NeuroVirology, 2011)

Association of FAK activation with lentivirus-induced disruption of blood-brain barrier tight junction–associated ZO-1 protein organization - Nathan S Ivey; Nicole A Renner; Terri Moroney-Rasmussen; Mahesh Mohan; Rachel K Redmann; Peter J Didier; Xavier Alvarez; Andrew A Lackner; Andrew G. MacLean (Journal of NeuroVirology, 2009)

Acquired immunodeficiency syndrome and the blood-brain barrier - Nathan S Ivey; Andrew G MacLean; Andrew A Lackner (Journal of NeuroVirology, 2009)

Venous but not skeletal muscle interstitial nitric oxide is increased during hypobaric hypoxia - Urs A. Leuenberger; Douglas Johnson; Joseph Loomis; Kristen S. Gray; David A. MacLean (European Journal of Applied Physiology, 2008)

Autotransgenic and allotransgenic manipulation of growth traits in fish for aquaculture: a review - Y. K. Nam; N. Maclean; G. Hwang; D. S. Kim (Journal of Fish Biology, 2008)
It is noteworthy that the use of transgene elements homologous to both the structural gene and promoter region sequences are more effective than heterologous ones for growth hormone (GH) transgenesis in farmed fish species. The generation of autotransgenic fish carrying the GH‐transgene construct (of which elements originate from the same species only) has been given considerable attention as a potential means to produce a desirable fish strain acquiring significantly improved growth phenotype. Currently, several growth‐enhanced autotransgenic lines including mud loach, carp and tilapia, have been developed or are ongoing for aquacultural purpose. This review considers the generation, development and prospects of autotransgenic manipulation of fish growth, comparing the growth performance of currently available autotransgenic fish strains with those of relevant fast‐growing allotransgenic fishes.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Correlating Material Properties with Tissue Composition in Enzymatically Digested Bovine Annulus Fibrosus and Nucleus Pulposus Tissue - Delphine S. Perie; Jeff J. Maclean; Julia P. Owen; James C. Iatridis (Annals of Biomedical Engineering, 2006)

Phylogeography, genetic structure, and diversity in the dhole ( Cuon alpinus ) - A. IYENGAR; V. N. BABU; S. HEDGES; A. B. VENKATARAMAN; N. MACLEAN; P. A. MORIN (Molecular Ecology, 2005)
The Asiatic wild dog or dhole was once very widely distributed across Asia but now has a very fragmented range. In this first genetic study of this little‐known species, we obtained information on genetic diversity, phylogeography, and social structure using both mitochondrial control region sequencing and microsatellite genotyping of noninvasive faecal samples from wild populations, as well as from museum and captive samples. A pattern largely consistent with isolation by distance across the Asian mainland was observed, with no clear subspecies distinctions. However, two major phylogeographical groupings were found across the mainland, one extending from South, Central, and North India (south of the Ganges) into Myanmar, and the other extending from India north of the Ganges into northeastern India, Myanmar, Thailand and the Malaysian Peninsula. We propose a scenario involving glaciation events that could explain this pattern. The origin of the dhole populations in Sumatra and Java is enigmatic and requires further study. Very low levels of genetic diversity were observed among wild dholes from Baluran National Park in Java, Indonesia, but in contrast, high levels were observed in Mudumalai Wildlife Sanctuary in South India.

Estimation of the repeatability and reproducibility of three diagnostic tests for infectious salmon anaemia virus - P Nérette; I Dohoo; L Hammell; N Gagné; P Barbash; S MacLean; C Yason (Journal of Fish Diseases, 2005)
Reverse transcriptase polymerase chain reaction (RT‐PCR), virus isolation (VI) and indirect fluorescent antibody tests (IFAT) are three assays currently used by the salmon industry to identify fish infected with infectious salmon anaemia virus (ISAV). However, no data are available on the repeatability (within‐laboratory consistency) and reproducibility (between‐laboratory consistency) of these assays and very limited information is available on the effect of freezing samples on test results. In order to evaluate these assays, five laboratories participated in a blinded study of 400 kidney samples representing four populations of farmed Atlantic salmon with different prevalence of ISAV. Each laboratory used its own testing protocols. Repeatability and reproducibility were evaluated using kappa as the measure of agreement. The effect of freezing was evaluated using the McNemar test. Freezing did not affect VI but improved the sensitivity of RT‐PCR. The repeatability and reproducibility of VI was almost perfect. There was a substantial difference in repeatability of RT‐PCR among the three laboratories with kappa ranging from 0.5 to 0.96. The repeatability for RT‐PCR was generally low. The repeatability of IFAT was moderate when the results were analysed using 1+ and above as a positive result. The results of the study show the need to standardize the protocol and interpretation of RT‐PCR.

Comparison of reference genes for quantitative real-time polymerase chain reaction analysis of gene expression in sugarcane - Hayati M. Iskandar; Robert S. Simpson; Rosanne E. Casu; Graham D. Bonnett; Donald J. Maclean; John M. Manners (Plant Molecular Biology Reporter, 2004)

Mitochondrial DNA Clocks and the Phylogeny of Danaus Butterflies - Gugs Lushai; David A. S. Smith; Dave Goulson; John A. Allen; Norman Maclean (International Journal of Tropical Insect Science, 2003)

A computer‐activated food delivery system for dispensing natural prey items among complex arrays of patches - A. Maclean; M. S. Miles; J. D. Armstrong (Journal of Fish Biology, 2003)
Experimental studies of the foraging ecology of drift‐feeding fishes have been limited in scope because of the lack of systems for dispensing suitable prey items to a number of patches with complex and controlled spatio‐temporal patterns of delivery rate. Here, tests are reported of a computer‐controlled feeding system that performs this requirement with considerable flexibility.

Monitoring the in Vivo Delivery of Proteins from Carbomer Hydrogels by X-Ray Fluorescence - Donald S. MacLean-McDavitt; J. David Robertson; Michael Jay (Pharmaceutical Research, 2003)

Five new polymorphic microsatellite loci in the European hedgehog Erinaceus europaeus - M. Henderson; S. A. Becher; C. P. Doncaster; N. Maclean (Molecular Ecology, 2000)

Isolation of microsatellite markers from the Adonis blue butterfly ( Lysandra bellargus ) - G. L. Harper; S. Piyapattanakorn; D. Goulson; N. Maclean (Molecular Ecology, 2000)

Insulin does not regulate the promoter of Cholesteryl Ester Transfer Protein (CETP) in HIRc/pCETP-CAT cells - Paul S. MacLean; Hisham A. Barakat (Molecular and Cellular Biochemistry, 2000)

A suite of highly polymorphic microsatellite markers in turbot ( Scophthalmus maximus L.) with potential for use across several flatfish species - A. Iyengar; S. Piyapattanakorn; D. A. Heipel; D. M. Stone; B. R. Howell; A. R. Child; N. Maclean (Molecular Ecology, 2000)

Chromosomal localization of the Huntingtin Associated Protein (HAP-1) gene in mouse and humans with radiation hybrid and interspecific backcross mapping - J. Nasir; A. Maclean; S. Engelender; K. Duan; R.L. Margolis; J.J. Kleiderlein; C.A. Ross; M.R. Hayden (Mammalian Genome, 1999)

Methylglyoxal production in bacteria: suicide or survival? - G. P. Ferguson; S. Tötemeyer; M. J. MacLean; I. R. Booth (Archives of Microbiology, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Gene delivery to rat enteric neurons using herpes simplex virus-based vectors - M. Keith Howard; Robert S. Coffin; Alistair R. Maclean; S. Moira Brown; Doreen Bailey; Patricia N. Anderson; Geoffrey Burnstock; David S. Latchman (Journal of Molecular Neuroscience, 1997)